2007
DOI: 10.1080/02701367.2007.10599402
|View full text |Cite
|
Sign up to set email alerts
|

Feedback After Good Trials Enhances Learning

Abstract: Recent studies (Chiviacowsky & Wulf, 2002, 2005) have shown that learners prefer to receive feedback after they believe they had a "good" rather than "poor" trial. The present study followed up on this finding and examined whether learning would benefit if individuals received feedback after good relative to poor trials. Participants practiced a task that required them to throw beanbags at a target with their nondominant arm. Vision was prevented during and after the throws. All participants received knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
112
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(134 citation statements)
references
References 26 publications
10
112
1
5
Order By: Relevance
“…Interviews (with typical adults) conducted by Chiviacowsky and Wulf 17 (see also Patterson and Carter 32 ) indicated that participants (both self-control and yoked) preferred to receive feedback after good trials. In fact, subsequent studies demonstrated that learning was enhanced when feedback was provided after relatively good rather than poor trials 39 , presumably due to the enhanced intrinsic motivation resulting from "positive" feedback [40][41][42] . A preference for feedback after good trials was not evident for participants in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Interviews (with typical adults) conducted by Chiviacowsky and Wulf 17 (see also Patterson and Carter 32 ) indicated that participants (both self-control and yoked) preferred to receive feedback after good trials. In fact, subsequent studies demonstrated that learning was enhanced when feedback was provided after relatively good rather than poor trials 39 , presumably due to the enhanced intrinsic motivation resulting from "positive" feedback [40][41][42] . A preference for feedback after good trials was not evident for participants in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Human beings appear to have a propensity to prefer positive information about themselves, such as positive feedback about their performance (Chiviacowsky & Wulf, 2007) or physical fitness, athleticism, health, and physical attractiveness (Ennigkeit & Hänsel, 2014). While these preferences may simply imply a preference for states of positive over negative affect without performance implications, they may reflect people's (implicit) knowledge of the beneficial consequences of this type of feedback for motivation, performance, and learning.…”
Section: Interim Summary: Enhanced Expectanciesmentioning
confidence: 99%
“…An underappreciated function of feedback in the motor learning literature has been its influence on the performer's motivational state. In a series of recent studies, providing learners with feedback after "good" trials, compared with "poor" trials, resulted in more effective learning (Badami, VaezMousavi, Wulf, & Namazizadeh, 2012;Chiviacowsky & Wulf, 2007;Chiviacowsky, Wulf, Wally, & Borges, 2009;Saemi, Porter, Ghotbi-Varzaneh, Zarghami, & Maleki, 2012;Saemi, Wulf, Varzaneh, & Zarghami, 2011). In those studies, feedback about task performance was given after blocks of trials.…”
Section: Positive Feedbackmentioning
confidence: 99%
“…According to the evidence, repetition of a good performance pattern is easier than changing a performance pattern for correcting error. In addition, it leads to implicit learning (Chiviacowsky & Wulf, 2007). Furthermore, the findings the present study indicated that most of the participants tend to receive feedback after their good trials rather than their weak trials.…”
Section: Discussionmentioning
confidence: 64%
“…Probably, another factor influential in the superiority of the group with good trials over the group with poor trials is the subjects' tendency to receive feedback after their good trials (Badami et al, 2011;Chiviacowsky & Wulf, 2005). The superiority of the group with feedback after good trials over the group with feedback after poor trials may originate from the motivational effect of feedback (Badami et al, 2012;Chiviacowsky & Wulf, 2007) and the probable escalation of self-confidence in the group with the feedback after the good trials which left its effect in the retention test upon removal. Successful experience increase self-confidence and the beliefs which form in the subject on account of the kind of feedback anticipate the function (Fitzsimmons, Landers, Thomas, & van der Mars, 1991).…”
Section: Discussionmentioning
confidence: 99%